2020
DOI: 10.1002/jbmr.3984
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Obesity Is Associated With an Increased Risk of Childhood Fracture: A Longitudinal Cohort Study of 466,997 Children and Up to 11 Years of Follow-up in Catalonia, Spain

Abstract: This study aimed to determine if having an overweight or obese range body mass index (BMI) at time of beginning school is associated with increased fracture incidence in childhood. A dynamic cohort was created from children presenting for routine preschool primary care screening, collected in the Information System for Research in Primary Care (SIDIAP) platform in Catalonia, Spain. Data were collected from 296 primary care centers representing 74% of the regional pediatric population. A total of 466,997 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 85 publications
2
25
0
1
Order By: Relevance
“…Previous results on BMI and fracture risk in healthy children are controversial. There is evidence that overweight and obese children have higher risk for upper and lower limb fractures, (15) whereas another study reported decreased fracture risk in obese children and increased fracture risk in children with underweight. (16) In our cohort of children and young adults with T1D, no significant relation between BMI and fractures could be detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results on BMI and fracture risk in healthy children are controversial. There is evidence that overweight and obese children have higher risk for upper and lower limb fractures, (15) whereas another study reported decreased fracture risk in obese children and increased fracture risk in children with underweight. (16) In our cohort of children and young adults with T1D, no significant relation between BMI and fractures could be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the associations of body mass index (BMI) or concomitant pathology such as celiac disease with fracture risk in children with T1D is still controversial. (15)(16)(17)(18) The aim of this study was to evaluate the age distribution and most common fracture sites in children and young adults with T1D. Additionally, associations of fractures with metabolic control, physical activity, and smoking, as well as diabetes complications and comorbidity among children and young adults with T1D were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, obesity significantly limited fracture repair, with no callus or connected bone observed in obese mice days after fracture unlike control animals. 81 High levels of limb fractures are also observed in obese children, [82][83][84] where abnormal BMAT and adiponectin levels may be contributing to reduced bone strengthen and delayed repair.…”
Section: Role Of Adiponectin In the Regulation Of Bone Homeostasismentioning
confidence: 99%
“…Childhood obesity is one of the most worrying public health problems of the century. Its burden stems from its immediate influence on the psychological, dental and skeletal wellbeing, its persistence in adolescence years, and its positive association with noncommunicable diseases and mortality in adulthood [1][2][3][4][5]. Early identification of obesity plays a key role in controlling the disease at a time when lifestyle practices get established.…”
Section: Introductionmentioning
confidence: 99%